Coding Based PBL Model for Numeracy and Computational Thinking: Model PBL Berbasis Coding untuk Numerasi dan Computational Thinking - Putri, Vivien Harianika; Wiryanto, Wiryanto; Puspita, Ari Metalin Ika (Academia Open, 2026)
General Background: Twenty-first century education requires students to develop numeracy literacy and computational thinking as essential competencies aligned with technological advancement. Specific Background: In Indonesia, national assessments and PISA data indicate that students’ numeracy skills remain at a moderate level, necessitating innovative pedagogical approaches such as Problem Based Learning integrated with coding activities, including unplugged coding. Knowledge Gap: Previous studies have predominantly examined Problem Based Learning and coding separately, with limited research integrating both approaches simultaneously in elementary numeracy learning. Aims: This study aims to analyze the use of a coding-based Problem Based Learning model on numeracy and computational thinking abilities of fifth-grade elementary students. Results: Using a quasi-experimental non-equivalent control group design, the findings show higher gain scores in the experimental group compared to the control group for numeracy (20.53 vs 8.37) and computational thinking (25.41 vs 9.66), with statistically significant differences (p < 0.05). Novelty: The study offers a unified instructional model combining Problem Based Learning and unplugged coding to simultaneously measure numeracy and computational thinking outcomes in elementary education contexts with limited digital infrastructure. Implications: The findings provide theoretical contributions to integrated learning models and practical guidance for teachers and institutions in implementing contextual, problem-based, and coding-supported instruction to strengthen numeracy and computational thinking in primary education. Highlights Higher learning gains observed in experimental group for both measured competencies Structured algorithmic activities support systematic problem solving processes Integrated approach applicable without reliance on digital infrastructure Keywords Problem Based Learning; Coding; Unplugged Coding; Numeracy; Computational Thinking